The Analytical Aspect of the International High-Tech Marketing in Europe - Khadzhynov Illya V. (Bìznes Inform, 2019)
For many new established companies and those working in the market for a long period of time, improving the efficiency of marketing activities is one of the main tasks on the way to high competitiveness. In such circumstances, there is a choice – increase the cost of promotion and advertising or reorganize the trade group. For high-tech companies, the task of becoming efficient in marketing activities, using the international marketing instrumentarium, often starts from scratch. Such companies tend to draw their initial strength from the innovations that are provided by research and development. In an inthety chaotic and rapidly changing competitive environment, the importance of research and development cannot be overstated. But when a competitive environment becomes more orderly, marketing function also becomes important for high-tech companies. The publication is concerned with the issues of development of the high-tech market and related services in Europe in the time period between 2004 and 2015. The creation of new technologies, their efficient use and market entry are the most important factors in global competitiveness. High-tech sectors and enterprises are key drivers of economic growth and productivity and tend to provide high value-added and well-paid employment of the population.